1984
DOI: 10.1037/0012-1649.20.4.575
|View full text |Cite
|
Sign up to set email alerts
|

A reexamination of developmental changes in causal attributions.

Abstract: The current study examined young children's use of the presence or absence of extrinsic reward to make inferences about the intrinsic motivation of another person. Previous research indicates that most kindergartners do not use a discounting heuristic, but it was hypothesized that they may have misinterpreted the questions asked. Kindergarten, second, and fourth graders were presented stories about children who were rewarded or not rewarded for performing various activities Two forms of questioning about motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
3

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
2
9
0
3
Order By: Relevance
“…Kassin, Lowe, & Gibbons, 1980;Kelley, 1973), and cognitive bias theory (Curtis & Schildhaus, 1980;Dalenberg et al, 1984) are consistent with this pattern and may underlie it. Speci cally, children described as aggressive and ill were rated as behaving more properly than expected and were rated as more acceptable than an additive model would predict.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Kassin, Lowe, & Gibbons, 1980;Kelley, 1973), and cognitive bias theory (Curtis & Schildhaus, 1980;Dalenberg et al, 1984) are consistent with this pattern and may underlie it. Speci cally, children described as aggressive and ill were rated as behaving more properly than expected and were rated as more acceptable than an additive model would predict.…”
Section: Discussionmentioning
confidence: 52%
“…Discounting, an attribution principle (e.g. Kassin, Lowe, & Gibbons, 1980;Kelley, 1973), and cognitive bias theory (Curtis & Schildhaus, 1980;Dalenberg et al, 1984) are consistent with this pattern and may underlie it. These theories suggest that when presented with an aggressive chronically ill child, the peer may attribute the aggressive behaviour to illness, removing blame from the child and potentially decreasing peer rejection (e.g.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, young children are often required by their parents or other adults to offer apologies to one another (‘Say you're sorry’). In this case, it is possible for children to simply echo the words without fully understanding their pragmatic implications and for others to interpret their utterances as obedience to authorities and rather than sincere expressions of regret (Dalenberg, Bierman, & Furman, 1984; Karniol & Ross, 1976, 1979). We sought evidence, in the apologies offered and in siblings' reactions to them, of children's sensitivity to the functions served by apologies and the meaning associated with various forms of apologies.…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of such a schema is thus tied to a particular level of cognitive development and the skills that define it. In contrast, however, experiments designed to "simplify" the stimulus and response components of the discounting task have met with a good deal of success (e.g., Dalenberg, Bierman, & Furman, 1984;Karniol & Ross, 1979;Kassin & Gibbons, 1981;Shultz & Butkowsky, 1977)-enough to suggest that, at the very least, preschool-age children have the "capacity" to discount in their social perceptions. This kind of position was advanced by Morgan (1983), who concluded that "young children may not possess the cognitive structures postulated by the self-perception models" (p. 818).…”
mentioning
confidence: 99%